Kebijakan Penataan Regulasi Pajak Daerah sebagai Upaya Peningkatan Pendapatan Asli Daerah - Bhim Prakoso (Fakultas Hukum Universitas Islam Jember, 2018)
Philosophically, regional tax is a mandatory contribution to the region that is owed by an individual or an entity that is compelling based on the law by not getting direct compensation and used for regional needs for the greatest prosperity of the people. Regional Tax as one of the components of local revenue receipt (hereinafter abbreviated as PAD), the potential for regional tax collection provides more opportunities for regions to be mobilized to the maximum when compared to other PAD revenue components. The role of local governments in exploring and developing various regional potentials will greatly determine the success of the implementation of government tasks, development and community services in the regions.Some of the main functions of taxes in supporting development in the region are the first tax function as a budget, namely to finance State expenditures. Second, the function regulates that is to lead investors to invest in supporting economic growth. Third, the stabilization function is to control inflation in order to maintain economic stability. Fourth, the distribution function is to open employment opportunities so as to increase people's income. According to the tax functions above if an error occurs both in management and implementation, it will reduce or even eliminate the function carried by the tax so that expectations according to the tax function do not materialize.Being a problem is how much the ability of the budgetair functions, regulated (regulated), stabilization and distribution of taxes is created in the regional economy and how much the ability of taxes to encourage regional economic growth. Therefore to increase local taxing power in regional taxes there are several things that must be considered, namely 1) The importance of more intensive tax socialization to increase literacy regarding regional taxes; 2). While inclusion is the ease of access to tax information systems, reporting of business income in a more real way to the payment system made on-line: 3) Tax information systems are integrated with the management of opening business licenses and business extensions. Keywords: regulation, regional tax, welfare.